Diversity of weevils (Coleoptera: Curculionidae) in orchards of pecanero walnut in the north of Coahuila, Mexico - Soto-Hernández Macotulio; Barros-Barrios Mayelis María (Revista Mexicana de Ciencias Agrícolas, 2018)
The northern region of Coahuila is one of the most important nut producing areas in Mexico. Euplatypus segnis (Chapuis, 1865) and Xyleborus ferrugineus (F. 1801) curculionids plague associated with walnuts in the country, not knowing if there are others present in the orchards. From july 2015 to september 2016 and august 2017, samples were taken from the Germplasm Bank of the INIFAP-Experimental Zaragoza Site, eight commercial orchards and native walnut trees. Using as sampling methods standard entomological network and knocking-sprinkling of the foliage with Cipermetrina. The 1 174 adult insect specimens were collected, six orders were determined, 49% were coleoptera, with Coccinellidae being the most abundant family, 17% were curculionids (203 adults and 32 identified species). Pandeleteius cinereus (Horn, 1876), Compsus auricephalus (Say, 1824) and Conotrachelus leucophaetus (Fahraeus, 1837 were harvested in walnut foliage, currently these species are not of economic importance for the crop. Smicronyx interruptus (Blatchley, 1916), S. sculpticollis (Casey, 1892) and Thecesternus hirsutus (Pierce, 1909) are possible natural biological control agents for Cuscuta L., 1753, Acacia (Mill, 1754) and Parthenium L., 1753. It is important that no specimens were collected from Curculio caryae (Horn, 1873), Euplatypus segnis, neither Xyleborus ferrugineus, curculionidae considered pests of pecan tree in Mexico.